PEMBERDAYAAN PESANTREN DALAM MEWUJUDKAN GURU BAHASA ARAB PROFESIONAL BERBASIS METODE PEMBELAJARAN BAHASA ARAB KREATIF DAN INOVATIF (DI PESANTREN AL HIDAYAH SUKOREJO PASURUAN) - Nur Hasan (VICRATINA, 2019)
Education is closely related to an effort to advance the nation. Through character education, it is hoped that the future generations can become great leader. Learning about formal education and integrating religious values is expected to be able to encourage students to have strong character based on religiousvalues. That is what state 5 high schools Malang do, in an effort to develop student character.Hopefully this can be an example for other schools in an effort to develop student character. One of the non-formal education that is quite successful in educating students is Islamic Boarding Schools, where students can study religion as a whole starting from learning the Koran, Hadith, Jurisprudence, Arabic, Nahwu Sharaf, and other religious studies tirelessly. Therefore Islamic boarding schools are considered to have potential human resources in realizing professional Arabic language teachers who can improve the quality of Arabic language learning in Indonesia compared to Arabic teachers who have never been educated in boarding schools. But unfortunately there are still a number of pesantren that are still weak in the field of actual, creative, innovative Arabic language learning methodologies. This is important to be adopted so that the output of santri can later be competent in the field of mastering the actual methods or styles of Arabic learning. This service was carried out at Al Hidayah Islamic Boarding School, Sukorejo Subdistrict, Pasuruan Regency by using the action review method which aims to improve the skills of the santri through creative, innovative methods in learning Arabic. The results of this service are first. Socialization of Arabic language learning methodology for non-arabic speakers. Second Socialization of the Use of Learning Media and thirdly Creating Arabiyyah Biology (language environment) and the results of this service is the first Socialization of Arabic language learning methodology for non-arabic speakers, both Socialization of Learning Media Usage, and third Creating Arabiyyah Biology (language environment). Keywords : empowering, arabic language teachers, creative, innovative